Lessons from four decades of monitoring vegetation and fire: maintaining diversity and resilience in Florida's uplands. Issue 2 (2nd February 2021) - Abrahamson, Warren G.; Abrahamson, Christy R.; Keller, Matthew A.
Abstract: Worldwide, humans are altering the fire regimes (fire‐return intervals, severity, seasonality) of fire‐prone ecosystems, fragmenting natural landscapes, and altering climates. Efforts to restore fire regimes in natural areas are usually guided by fire management plans (FMP) that rely on prescribed burning. Despite the common use of FMPs, limited efforts have gone to assessing vegetative and faunal responses. While some insights into responses to fire from short‐term studies are available, there is less knowledge about FMP outcomes applied over multiple decades. Peninsular Florida hosts many fire‐prone communities including globally threatened Florida scrub. We repeatedly sampled species composition and abundance during a 38‐yr period (1977–2015) at 11 upland stands including wet prairies, flatwoods, and Florida scrub (i.e., oak scrub, rosemary scrub, hickory scrub). A total of 22 fires impacted the stands with individual stands experiencing as few as 2 and up to 11 fires. There was no invasion of non‐native plants following fires and stands showed remarkable ecological resilience with limited change in species composition and modest abundance shifts due to differential recovery rates. Importantly, ecological resilience was not eroded with repeated fire. Species richness, evenness, and diversity were significantly higher at the end vs. beginning of our study, suggesting that current fire regimes are within the range of those with which species evolved. While resprouting shrubs and trees persevered under a range of fire‐return intervals, an obligate‐seeding shrub was adversely impacted by fires more frequent than FMP‐recommended intervals. Several lessons are apparent from our findings. Best practice should: use the full range of fire‐return variation at evolutionarily appropriate intervals; utilize natural fire seasons to the extent possible; compare outcomes and modify prescriptions as necessary to meet FMP goals; give special consideration to burn units with embedded associations of widely differing fire regimes than principal associations in order to maintain diversity of both associations; and account for climate change in FMPs since fire behavior, frequency, and community responses to fire will likely change in the coming decades. Outcomes of FMPs must be carefully evaluated to ensure prescriptions are evolutionarily appropriate and to ameliorate the impacts of altered climates.